al-Majmūʻah al-kāmilah li-Majallat Abūllū. - Sharaf, ʻAbd al-ʻAzīz, al-Duktūr.; Khafājī, Muḥammad ʻAbd al-Munʻim. (al-Hayʼah al-Misṛīyah al-ʻĀmmah lil-Kitāb, 2003)
The complete works of Apollo magazine.